The effect of massage for babies aged 3-6 months with lavender essential oil and lavender aromatherapy on the duration of infant sleep in the midwife's independent practice - Nabila Raniah; Ira Kusumawaty; Desy Setiawati (Journal of Maternal and Child Health Sciences (JMCHS), 2021)
Backgorund: One of the factors that greatly affect the growth and development of babies is rest and sleep. Good sleep is very important for baby's growth and development, one of the factors that can increase baby's sleep duration is by doing baby massage with lavender essential oil and lavender aromatherapy. Purpose: The purpose of this study was to determine the effect of baby massage with lavender essential oil and lavender aromatherapy on the duration of baby sleep in the midwife's independent practice. Methods: This research is a quantitative research using a quasiexperimental design research method and a pretest-posttest model with control group design. The research sample was baby who met the inclusion criteria totaling 32 people. Data were analyzed using Paired Sample t. Test statistical test. Results: Through bivariate analysis using paired sample t.testt on the respondents' sleep duration before and after baby massage with lavender essential oil and lavender aromatherapy to show that the significance value of is 0.009 (p≤ 0.05. Conclusion: There is an effect of massage with lavender essential oil on the duration of baby sleep. For further researchers, it is hoped that they can add more variables in research related to the duration of baby sleep.